2004
DOI: 10.1152/ajpcell.00321.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for functional estrogen receptors α and β in human adipose cells: regional specificities and regulation by estrogens

Abstract: Adipocytes are estrogen-responsive cells, but the quantitative expression and transcriptional regulation of the estrogen receptors (ER-alpha and ER-beta) in human adipocytes and their precursor cells are unclear. Using real-time quantitative PCR, we have demonstrated that both ER-alpha and ER-beta mRNA are expressed in human mature adipocytes with a large predominance of ER-alpha mRNA. Moreover, ER-alpha mRNA is identically expressed whatever the anatomic origin (intraabdominal and subcutaneous) of the adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
140
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 51 publications
(48 reference statements)
12
140
1
3
Order By: Relevance
“…7 ER mRNAs are expressed in mature human adipocytes where the ERa mRNA predominates. 8 ERa mRNA levels do not differ in adipocytes from different anatomical origins (intraabdominal or subcutaneous) or according to gender in non-obese individuals. 8 Women usually increase their body weight after menopause when oestrogen levels naturally decrease.…”
Section: Introductionmentioning
confidence: 85%
“…7 ER mRNAs are expressed in mature human adipocytes where the ERa mRNA predominates. 8 ERa mRNA levels do not differ in adipocytes from different anatomical origins (intraabdominal or subcutaneous) or according to gender in non-obese individuals. 8 Women usually increase their body weight after menopause when oestrogen levels naturally decrease.…”
Section: Introductionmentioning
confidence: 85%
“…Potential gene targets of E2 can be estimated by the expression and distribution of its receptors. Studies investigating the expression patterns of ER-a and ER-b showed that they are expressed in rat and human preadipocytes, mature adipocytes, and other cell types present in adipose tissue, including macrophages (Price and O'Brien 1993;Crandall et al 1998;Dieudonne et al 2004). Various studies have shown that E2 regulates adipocyte differentiation; however, the results are contradictory.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…Several lines of recent evidence suggest a potential role for ER-α in the determination of BMI. ER-α may play a critical role in adipose tissue development, metabolism, deposi tion [10,11] and energy metabolism [12] . The estrogen antagonist acting on ER-α can prevent diet-and ovariectomy-induced obesity, mainly by decreasing fat deposition [13] .…”
Section: Introductionmentioning
confidence: 99%